Exploring Double Consciousness: Capitalist Attitude and White Supremacy in Drama Serial Parizaad (Journal of Social Sciences Review, 2022)
The current research study explores the suffering of doubleconsciousness in the character of Parizaad in Pakistani Urdu drama serial,Parizaad. It is a story which unfolds Marxist, racist and sociological themes.However, the researcher has utilized a non-empirical Textual AnalysisMethod of research along with following the concept of double consciousnessby Du Bois as a theoretical framework for analyzing the drama serial toexplore the research objective. The framework argues that black people arebehaved racially which causes inferiority complex, second-sight and twonessin them. Similarly, the analysis of the drama serial in this research studymanifested that Pakistani brown people, following white legacy of racism,consider themselves superior to their fellow blackish people. Also, the powerof money is dominant, and such socio-economic factors cause doubleconsciousness in the character of blackish-skin Parizaad.
Keywords: Double Consciousness, Money, Mimicry, Parizaad, Pakistani Drama